2009
DOI: 10.3233/nre-2009-0464
|View full text |Cite
|
Sign up to set email alerts
|

Transcallosal fibers from corticospinal tract in patients with cerebral infarct

Abstract: Diffusion tensor image tractography (DTT) can visualize white matter tracts and provide a powerful vehicle with which to investigate the neural pathway at the subcortical level. We attempted to demonstrate the clinical significance of transcallosal fibers (TCF) originating from the corticospinal tract in patients with corona radiata infarct located below the corpus callosum, using diffusion tensor image tractography (DTT). Forty patients with corona radiata infarct located below the corpus callosum and 26 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…However, no optimal degree of tract turning angle has been reported; instead, TCMF tends to be easily changed by the tract turning angle (Lee et al, 2005). Therefore, we reconstructed the CST using the FA value of 0.2 and compared the incidence of TCMF using three different tract turning angles (45, 60, and 75°), which have been adopted popularly in other studies using DTT for the CST (Jang et al, 2009; Son et al, 2009; Kwon et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, no optimal degree of tract turning angle has been reported; instead, TCMF tends to be easily changed by the tract turning angle (Lee et al, 2005). Therefore, we reconstructed the CST using the FA value of 0.2 and compared the incidence of TCMF using three different tract turning angles (45, 60, and 75°), which have been adopted popularly in other studies using DTT for the CST (Jang et al, 2009; Son et al, 2009; Kwon et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Transcallosal motor fiber (TCMF), which indicates the connection fibers of the corpus callosum between primary motor cortices of the two hemispheres, plays a role in interhemispheric inhibition (IHI) between the two primary motor cortices (Netz, 1999; De Gennaro et al, 2004; Lenzi et al, 2007; Wahl et al, 2007; Wahl and Ziemann, 2008; Jang et al, 2009). IHI has been an important concept in development of the motor system of the brain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Impairments in M1-M1 and S1-S1 interhemispheric inhibition appear to contribute to motor deficits after stroke [12,14], but the effects of stroke on the integrity of CC motor and sensory fibres and their relation to motor function have not been thoroughly described. Jang et al [15] found that the presence of transcallosal fibers projecting from the unaffected corticospinal tract and descending towards the lesion were associated with poor motor function, but did not specifically evaluate the integrity of fibers within the callosum. Another study demonstrated that transcallosal M1-M1 fibre integrity was reduced in individuals with chronic stroke and that lower integrity of these tracts was associated with less improvement on the Wolf Motor Function Test (WMFT) following 5 consecutive days of non-invasive brain stimulation paired with physical therapy [16].…”
Section: Introductionmentioning
confidence: 99%